Pengaruh Model Problem Based Learning terhadap Keterampilan Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri 14 Sijunjung - Muhammad Nur Sulaiman Eato; Ena Noveria (AHKAM, 2025)
The low level of descriptive text writing skills among Grade VII students at SMP Negeri 14 Sijunjung is marked by difficulties in developing ideas, selecting appropriate vocabulary, and constructing well-structured sentences. To address these issues, this study aims to analyze the effect of the Problem Based Learning (PBL) model on students’ descriptive writing skills. A quantitative approach was employed using a quasi-experimental method with a One Group Pretest-Posttest design. The population consisted of 57 students, with the sample drawn from Class VII B. Data were collected through a performance-based descriptive text writing test and analyzed using a t-test. The results revealed a significant improvement in writing skills following the implementation of the PBL model, as indicated by an increase in the average score from the "fairly sufficient" category to "excellent." The hypothesis test showed a t value of 11.91, exceeding the t table value of 1.70, indicating a significant effect of the PBL model on students’ descriptive writing skills. These findings confirm that the Problem Based Learning model is effective in enhancing students’ abilities in terms of content, structure, and language use in descriptive texts. The implications suggest that teachers should consider integrating the PBL model as an alternative writing instruction strategy that promotes real-world problem-solving and active student engagement.